Prevalence of potentially serious alcohol–medication interactions in older adults in a community pharmacy setting: a cross-sectional study - Gráinne Cousins; Alice E Holton; Cora Keeney; Benedict Ryan (BMJ Open)
Objective Previous prevalence estimates of POtentially Serious Alcohol–Medication INteractions in Older adults (POSAMINO) are based on in-home inventories of medications; however, this method is associated with under-reporting of medications when compared with dispensing records. This study aims to estimate the prevalence of POSAMINO among community-dwelling older adults using drug dispensing data from the community pharmacy setting.Design Cross-sectional study.Setting Irish Community Pharmacy.Participants 1599 consecutive older adults presenting with a prescription to 1 of 120 community pharmacies nationwide; community-dwelling, aged ≥65 years, able to speak and understand English, with no evidence of cognitive impairment. The mean age of sample was 75.5 years (SD 6.5); 55% (n=884) female.Measures 38 POSAMINO criteria were identified using participants’ pharmacy dispensing records linked to self-reported alcohol consumption (beverage-specific quantity and frequency measures) over the last 12 months.Results The overall prevalence of POSAMINO in the study population was 28%, with 10% at risk of at least one POSAMINO criteria and 18% at risk of two or more. Exposure to POSAMINO most commonly involved cardiovascular agents (19%) and central nervous system agents (15%). Exposure to a higher number of POSAMINO criteria was associated with younger age (adjusted incident rate ratio (AIRR): 0.97; 95% CI: 0.95 to 0.98), male sex (AIRR: 0.55; 95% CI: 0.45 to 0.67) and a higher number of comorbidities (AIRR: 1.05; 95% CI: 1.01 to 1.13).Conclusion This study adds to the growing body of evidence, which suggests that older adults are vulnerable to potentially serious alcohol–medication interactions, particularly those involving cardiovascular and central nervous system agents, increasing their risk of orthostatic hypotension, gastrointestinal bleeds and increased sedation. Application of the POSAMINO criteria at the point of prescribing may facilitate the risk stratification of older adults and prioritise alcohol screening and brief alcohol interventions in those at greatest risk of harm.